Washback of Malaysia School-Based Assessment (SBA) on Form 4 students’ English language learning - Mohd Salleh, Nur Farisya Amylia (2022)
Washback refers to the impact of a test on its stakeholders. The test scores from the School-Based Assessment (SBA) have washback on how learners learn. School-Based Assessment is perceived as a holistic assessment to measure students’ cognitive, affective and psychomotor levels in a specific field of knowledge. The washback of School-Based Assessment has been studied among lower secondary students in Malaysia. However, previous studies have failed to examine the upper secondary school students in Malaysia. This study looks into the perception and attitudes of the upper secondary school students on the Malaysia School-Based Assessment (SBA) and aimed to investigate the washback of Malaysian Upper Secondary School-Based Assessment at a school in Selangor, Malaysia. This research could be considered a case study and focused primarily on the aspect of participants (students’ attitudes and perception towards the assessment) and products (the knowledge that had been learned that could contribute to the quality of learning). A group of Form 4 Malaysian English language learners (n = 142) were selected purposively. Generally, this study adapted mixed method, particularly sequential explanatory study design, where the qualitative data findings would be a mechanism to justify the statistical results. The data were collected via questionnaire, class observations and interviews. The questionnaire which is a five-point Likert scale, was adapted from Ying (2010). The questionnaire was then further analysed using descriptive statistics via Statistical Package for the Social Science (SPSS) 26, where further analysis of the Mean, Mode, Median and Standard Deviation of the items was made. The mean of the data was then classified and interpreted using Pimentel’s (2019) framework. The class observations and narrative recordings were then analysed using NVivo 11, where deductive thematic categorization was used for extracting the emerging themes. Ten students (n=10) were selected for the purpose of the interview session. The findings were then triangulated using Pan’s (2008) Holistic Model of Washback. They indicated that students reflected positive attitudes and perceptions towards SBA. However, some of the activities provided for the implementation of SBA were not supported with sufficient resources. Therefore, ‘resources’ are the main obstacle that the students are facing in order to undergo SBA in their English language learning. Also, peer feedback and constructive feedback from teachers constantly help learners in developing their skills in the English Language. The activities that SBA cater in class develops the students’ interest and motivation to learn the language.